Pendampingan Penerapan Inovasi Teknologi Pertanian Menuju Revolusi Industri 4.0 untuk Peningkatan Produksi Pangan - Muthia Amira Nasution; Nur Akhlul Nita Br Sembiring; Nazwa Aina Ramadhani Daulay; Inrika Aritonang; Andika Erlangga Erlangga; Solly Aryza (Cattleya Darmaya Fortuna, 2025)
The transformation of the agricultural sector toward the Industrial Revolution 4.0 has become a strategic necessity in addressing challenges related to increasing food demand, limited resources, and climate change. However, the adoption of modern agricultural technologies among farmers remains relatively low due to limited knowledge, skills, and access to technology. This community service program aims to enhance the capacity and productivity of farmer groups through assistance in implementing agricultural technology innovations based on Industry 4.0. The implementation methods include socialization of smart farming concepts, training on the use of Internet of Things (IoT)-based technologies for monitoring land and crop conditions, and hands-on assistance in applying the system directly in partner farming areas. Program evaluation was conducted by measuring improvements in farmers’ understanding, technology adoption rates, and comparisons of crop yields before and after technology implementation. The results indicate an increase in farmers’ knowledge and skills in utilizing agricultural technology, as well as improvements in land management efficiency and food production. Therefore, assistance in implementing Industry 4.0-based agricultural technology innovations serves as a strategic solution to support increased food production and sustainable farmer independence.